2021
DOI: 10.26633/rpsp.2021.133
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine hesitancy and acceptance in Mexico: a web-based nationwide survey

Abstract: Objective. To identify factors associated with COVID-19 vaccine hesitancy and acceptance among the Mexican population. Methods. In a web-based nationwide survey in early December 2020, respondents were inquired about their sociodemographic characteristics and their willingness to accept a hypothetical COVID-19 vaccine given a 50% or 90% effectiveness. A logistic regression model was used to identify the factors associated with hesitancy and acceptance. Results. A total 3 768 responses were analyzed. A 90% effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
37
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(50 citation statements)
references
References 18 publications
8
37
1
4
Order By: Relevance
“…As in previous studies, our research identified a subpopulation of vaccine-hesitant people in Mexico ( Fig. 2 C), albeit markedly smaller than those of other countries such as the United States (52.1%) or Russia (55.1%; Carnalla et al, 2021 ; Delgado-Gallegos et al, 2021 ; Ramonfaur et al, 2021 ; Sallam, 2021 ). The percentage of people with no VH (51.9%) was lower than that reported in other studies, such as those by Delgado-Gallegos et al (87.8%) or by Ramonfaur et al (85%; Delgado-Gallegos et al, 2021 ; Ramonfaur et al, 2021 ).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…As in previous studies, our research identified a subpopulation of vaccine-hesitant people in Mexico ( Fig. 2 C), albeit markedly smaller than those of other countries such as the United States (52.1%) or Russia (55.1%; Carnalla et al, 2021 ; Delgado-Gallegos et al, 2021 ; Ramonfaur et al, 2021 ; Sallam, 2021 ). The percentage of people with no VH (51.9%) was lower than that reported in other studies, such as those by Delgado-Gallegos et al (87.8%) or by Ramonfaur et al (85%; Delgado-Gallegos et al, 2021 ; Ramonfaur et al, 2021 ).…”
Section: Discussionsupporting
confidence: 83%
“…2 C), albeit markedly smaller than those of other countries such as the United States (52.1%) or Russia (55.1%; Carnalla et al, 2021 ; Delgado-Gallegos et al, 2021 ; Ramonfaur et al, 2021 ; Sallam, 2021 ). The percentage of people with no VH (51.9%) was lower than that reported in other studies, such as those by Delgado-Gallegos et al (87.8%) or by Ramonfaur et al (85%; Delgado-Gallegos et al, 2021 ; Ramonfaur et al, 2021 ). To understand this discrepancy, we must consider that all of them—including the present study—have limitations; for example, those studies were conducted before the vaccine rollout in Mexico and only considered VH as absent or present.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Having comorbidity was the prominent variable associated with higher vaccine acceptance. 30 , 42 On the contrary, this study showed having comorbidity was more likely to have COVID-19 vaccine hesitancy. In Indonesia, misinformation about the safety of COVID-19 vaccines has existed since vaccines were not available, such as disinformation and perceived vaccine unsafety for an individual having pre-existing comorbid conditions.…”
Section: Discussioncontrasting
confidence: 66%
“…Vaccine willingness decreases as vaccine effectiveness decreases. 20 , 30 Respondents who did not believe in the vaccine halalness were significantly more at risk of having vaccine hesitancy than the respondents having a belief in its halalness. Being a country with a Muslim majority population, a religious-based view about the halalness of COVID-19 vaccines could influence the vaccine’s acceptance.…”
Section: Discussionmentioning
confidence: 95%